Description of Factors Influencing Do Not Resuscitate (DNR) Decisions and Their Legal Consequences - Margaretha Indah Wijilestari; Yohanes Leonard Suharso; Hari Pudjo Nugroho (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: Do Not Resuscitate (DNR) is a clinical decision that often becomes an ethical, moral, and legal dilemma for medical personnel. This study aims to provide an overview of factors that influence DNR decisions and their legal consequences in Indonesia. This study is an empirical juridical research based on the medical record of several patients with each different diagnoses who were treated in the Emergency, Intensive Care Unit, Inpatient Installation, and Covid-19 Isolation Room. Furthermore, a normative juridical analysis is carried out using legal sources in force in Indonesia. The study results are the description of patient, family, care professional, resource, and bioethical understanding factors that influence DNR decisions. The consequences of criminal law are possible if the DNR is carried out without a strong clinical reason and the correct procedure as stipulated in the Regulation of the Minister of Health Number 37 of 2014. Therefore, doctors and hospitals must ensure DNR decisions are made on patients in a condition that cannot be cured due to the illness (terminal state) and medical action is futile; decisions are involved by all relevant hospital organs (Professional Team of Care Providers, Patient Services Manager, Director, Medical Committee, Ethics and Legal Committee); and based on the patient's family's written decision.Keywords: Do Not Resuscitate (DNR), influencing factors, legal consequences Abstrak: Do Not Resuscitate (DNR) merupakan keputusan klinis yang sering menjadi dilema etik, moral, dan hukum bagi para tenaga medis. Penelitian bertujuan untuk memberikan gambaran faktor yang mempengaruhi keputusan DNR dan bagaimana konsekuensi hukumnya di Indonesia ketika keputusan terpaksa dipilih. Penelitian menggunakan metode yuridis empiris berdasarkan rekam medis beberapa pasien dengan masing-masing diagnosis berbeda yang dirawat di Instalasi Gawat Darurat, Intensive Care Unit, Instalasi Rawat Inap, dan Ruang Isolasi Covid-19. Selanjutnya dilakukan analisis secara yuridis normatif dengan menggunakan sumber hukum yang berlaku di Indonesia. Hasil penelitian ini adalah ditemukannya gambaran faktor pasien, faktor keluarga, faktor tenaga profesional pemberi asuhan, faktor sumber daya, dan faktor pemahaman bioetika yang mempengaruhi keputusan DNR. Konsekuensi hukum pidana adalah mungkin, bila DNR dilakukan tanpa alasan klinis yang kuat dan tidak dilakukan dengan prosedur yang benar sebagaimana diatur dalam Peraturan Menteri Kesehatan Nomor 37 Tahun 2014. Oleh karena itu, dokter dan rumah sakit harus memastikan keputusan DNR dilakukan pada pasien yang berada dalam keadaan yang tidak dapat disembuhkan akibat penyakit yang dideritanya (terminal state) dan tindakan kedokteran sudah sia-sia (futile); keputusan melibatkan semua organ rumah sakit terkait (Tim Profesional Pemberi Asuhan, Manajer Pelayanan Pasien, Direktur, Komite Medik, Komite Etik dan Hukum); dan berdasarkan keputusan tertulis keluarga pasien.Kata Kunci: Do Not Resuscitate (DNR), faktor-faktor yang mempengaruhi, konsekuensi hukum